Luxembourg : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2017)
This Selected Issues paper studies diversification in Luxembourg's economy and the role of the government. The economy of Luxembourg appears to be more concentrated than that of comparable countries. Sectoral output is more concentrated than in other countries; this relative lack of diversification is true even when the financial sector is excluded and even compared with other European countries with a small population. However, employment concentration is similar to that in other countries. Luxembourg specializes in sectors whose labor productivity is somewhat higher than in several benchmark countries. The government should continue to further diversify the economy by fostering an environment for growth.